Analysis Of The Feasibility Of Corn Farming In Ruguk Village, Ketapang District, South Lampung Regency - Wayan Ekayana; I Wayan Suparta; Resha Moniyana Putri (Cita konsultindo, 2025)
This study aims to analyze the feasibility of corn farming in Ruguk Village, Ketapang District, South Lampung Regency. As an agricultural country, Indonesia has an agricultural sector that plays an important role in the economy, where corn is one of the strategic commodities. This study was conducted using a non-discounted business feasibility analysis method, which includes analysis of income, costs, and profits from corn farming. The results of the study showed that the income from corn farming in Ruguk Village was positive and had the potential to be developed. From the feasibility analysis, the Benefit Cost Ratio (B/C Ratio) value was 2.54, which indicates that every Rp 1 of costs incurred produces a net benefit of Rp 2.54. In addition, the Break Even Point (BEP) in terms of quantity was 4,506.7 kg, and the Return On Investment (ROI) reached 153.3%, which indicates that corn farming in this village is feasible to be further developed. This study is expected to provide information and input for farmers and the government in developing corn farming businesses, as well as improving the welfare of the community in Ruguk Village.